Antidermatophyte and antioxidant activities of Nigella sativa alone and in combination with enilconazole in treatment of dermatophytosis in cattle - Balikci, E. (Czech Academy Agricultural Sciences, 2016)
The purpose of this study was to comparatively assess the antidermatophyte and antioxidant activities of enilconazole, Nigella sativa (NS) and enilconazole with NS in the treatment of dermatophytosis in cattle. A total of 24 cattle with clinically established diagnosis of dermatophytosis were used in the study. Trichophyton verrucosum was isolated and identified from all of the specimens stemming from the dermatophytosis-suspected animals. The lesion areas in Groups 1, 2 and 3 were treated as follows: enilconazole (three times at 3-day intervals), NS (once a day for two weeks) and enilconazole with NS, respectively. There were significant increases (P < 0.05) in plasma aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase levels and non-significant increases (P > 0.05) in creatinine and blood urea nitrogen levels after treatment in Group 1 when compared with Groups 2 and 3. After treatment, glutathione peroxidase, superoxide dismutase, glutathione levels increased (P < 0.05) and plasma thiobarbituric acid reactive substances levels decreased (P < 0.05) in Groups 1, 2 and 3 in comparison with before treatment. However, there were significant decreases (P < 0.05) in plasma thiobarbituric acid reactive substances levels and significant increases (P < 0.05) in glutathione peroxidase, superoxide dismutase, glutathione levels after treatment in Groups 2 and 3 when compared with Group 1. This study indicates that NS might have antidermatophyte and antioxidant effects in the treatment of dermatophytosis in cattle and the antidermatophyte effects of NS plus enilconazole was stronger among all groups.
Keywords: Nigella sativa; enilconazole; antioxidants; trichophytosis; bovine